Accidental safety factors and prevention techniques for high-rise building projects â A review - Manzoor, B. (Ain Shams University, 2022)
Construction is a dangerous occupation due to the unique nature of the activities involved and the repetition of several construction activities. The development of construction industry has a direct impact on the country's economy and thus plays an important role in its growth. The construction industry, on the other hand, is dangerous due to the high rate of accidents and fatalities, as evidenced by alarming accident and fatality statistics. This scenario emphasizes the importance of identifying the safety factors that contribute to accidents in high-rise building projects. As a result, the research was split into two phases. The first phase of the study was concerned with the safety factors that influence accidents in high-rise building projects, and the second phase was concerned with safety prevention techniques that can be used to mitigate the safety factors that influence accidents in high-rise building projects. In addition, a framework has been proposed to aid construction project managers in evaluating the safety factors associated with high-rise building projects. As a result, this framework established a foundation for future researchers to use in high-rise building projects. Â© 2022 THE AUTHORS